(untitled) (Journal of actual problems of jurisprudence, 2018)
Article is devoted to consideration of separate problems of the conceptual and categorial device used in the criminal, criminal procedure and operational search legislation of the Republic of Kazakhstan. By means of the comparative and structural analysis the contradictions and gaps in the legislation complicating interpretation and use of standards of the criminal, criminal procedure and operational search legislation in practice are revealed. Key words: criminal offense, crime, operational search activity, operational search action, criminal case, pre-judicial investigation.